The Power Of CRM And Service Innovation Capabilities Toward Agencies’ Sales Performance In Products Marketing - Komarudin Komarudin; Yani Restiani Widjaya (Jurnal Computech & Bisnis (e-Journal), 2018)
This study focuses on three variables that serve as a framework of thinking of Customer Relationship Management as independent variables, Service Innovation Capabilities and Agencies’ Sales Performance  as a dependent variable. The object of the research is the marketing agency TIKI Bandung in Bandung Raya area with a sample of 32 marketing agencies. Data collection techniques using questionnaires and then processed with data analysis techniques structural equation modeling (SEM) using Smart PLS 3.0 software. The results in this study indicate the existence of positive   and   significant   impact   CRM   and   Innovation   Capabilities   to   Sales Performance marketing agency. Keyword : Customer Relationship Management, Innovation Capabilities, Sales Performance, Marketing Agency.